Non-specialized inpatient care provided by university hospitals in Japan - Shin-ichi Toyabe (Dove Medical Press, 2008)
Shin-ichi ToyabeCrisis Management Office, Niigata University Hospital, Niigata City, JapanAbstract: In Japan, all citizens are covered by the national insurance system in which universal free access to healthcare services is promised to everybody. Even in tertiary care university hospitals, considerable numbers of secondary care inpatients are supposed to be treated. We studied the mixed state of secondary care and tertiary care in university hospitals in Japan and its year-to-year trend. Based on the results of a national survey, we could statistically classify Japanese case-mix classification into 821 groups that are supposed to need tertiary care (group A) and 296 groups that are supposed to need secondary care (group B). Sixty percent of patients admitted to the university hospitals belonged to group A, and 25% belonged to group B. Despite of the implementation of government policies to differentiate functions of hospitals, there was no trend toward an increase in the rate of tertiary care and decrease in the rate of secondary care from 2003 to 2006. Patient behavior to seek tertiary care was simply influenced by distance from university hospital. However, behavior of patients to seek secondary care was significantly influenced by distance to adjacent general hospitals and seize of these hospitals.Keywords: inpatient care, Japan, university hospitals, patient behavior